2013
DOI: 10.1111/ahg.12000
|View full text |Cite
|
Sign up to set email alerts
|

Initial Assessment of the Pathogenic Mechanisms of the Recently Identified Alzheimer Risk Loci

Abstract: SUMMARY Recent genome wide association studies have identified CLU, CR1, ABCA7 BIN1, PICALM and MS4A6A/MS4A6E in addition to the long established APOE, as loci for Alzheimer’s disease. We have systematically examined each of these loci to assess whether common coding variability contributes to the risk of disease. We have also assessed the regional expression of all the genes in the brain and whether there is evidence of an eQTL explaining the risk. In agreement with other studies we find that coding variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 69 publications
4
37
2
Order By: Relevance
“…Examining the neuropathologic effects (if any) of these genes (and polymorphisms and amino acid changes within them) will be a challenge to neuropathologists. As Holton et al (94) have stated, "Measuring changes in damage induced expression in tissue with changing cell populations and developing rigorous algorithms to interpret such data is problematic." One of the most interesting observations has been that variants in triggering receptor expressed on myeloid cells 2 (TREM2) result in susceptibility to late-onset AD (95,96,97).…”
Section: Figurementioning
confidence: 99%
“…Examining the neuropathologic effects (if any) of these genes (and polymorphisms and amino acid changes within them) will be a challenge to neuropathologists. As Holton et al (94) have stated, "Measuring changes in damage induced expression in tissue with changing cell populations and developing rigorous algorithms to interpret such data is problematic." One of the most interesting observations has been that variants in triggering receptor expressed on myeloid cells 2 (TREM2) result in susceptibility to late-onset AD (95,96,97).…”
Section: Figurementioning
confidence: 99%
“…Recent GWA studies have identified CLU, CR1, ABCA7 BIN1, PICALM and MS4A6A/MS4A6E in addition to the long-established ApoE as loci for AD [39][40][41][42]44].…”
Section: The Genetics Of Admentioning
confidence: 99%
“…However, other than the wellestablished APP, MAPT, APOE, and closely related genes, the role of the vast majority of genes in AD remain unclear. The elucidation of the functional consequence of the genetic variations in the top GWAS genes has also proven to be challenging [5]. In light of the negative outcome of clinical trials with drugs targeting A␤ and tau, it becomes imperative to pursue alternative drug targets [6].…”
Section: Introductionmentioning
confidence: 99%